A practical application of domestic science - Mather, Myrtle (My University, 1902)
Introduction: We read in Holy Writ of the busy woman, and to judge from Solomon’s description not even the most up-to-date club woman of today has more to do than that “virtuous woman” whom he describes. One who worked willingly with her hands; who arose while it was yet night to give meat to her household; who bought a field and planted it with her hands; who clothed her household with scarlet; and herself with purple and silk; and who made fine linen to sell. The husband of this remarkable woman “sat among the elders of the land”, which is not surprising since we think he had nothing else to do. He praised his wife, and her children arose and called her blessed. Probably this was a sufficient reward for all the labor she performed, but we seem to have drifted away from that pleasant arrangement, regardless of the fact that the wants of the human family are the same today that they were four thousand years ago. The family must be fed and clothed; guarded against the snow and the heat; the husbands sit among the elders and are known in the gates, and the problems of living must be solved by women. In the light of modern learning we have placed this problem in the category of Domestic Science, and when its principles are rightly understood, its devotees expect the millennium dawn. To those who are outside the pale, Domestic Science means a collection of theories that are beautiful to talk of and write about, but are not suited to real practical living. What a mistaken idea!
Citation: Mather, Myrtle. A practical application of domestic science. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Home Economics; Domestic Science; Theses